Intrafamilial transmission and clustering of COVID-19: a socioepidemiological perspective - Hiram J Jaramillo-Ramírez; Beatriz H Kushida-Contreras; Aranza E García-Aréstegui; Gisel V Licón-Martínez; Miguel A Gaxiola-García (Journal of Infection in Developing Countries)
Introduction: The dynamics of COVID-19 transmission occurring in familial clusters may be related to sociodemographic and epidemiological characteristics of cases and contacts. The aim of this study was to identify the dynamics of COVID-19 transmission in families with more than one documented case.